A yoga-based exercise program for people with chronic poststroke hemiparesis. - Bastille JV; Gill-Body KM (Physical Therapy, 2004)
BACKGROUND AND PURPOSE: This was a preliminary investigation of the effects of a yoga-based exercise program on people with chronic (greater than 9 months) poststroke hemiparesis. Many people who have had a stroke report an impaired health status because of a reduced level of activity. Proponents of yoga contend that it offers a gentle alternative exercise program that can be easily adapted for people who have had a stroke. SUBJECTS AND METHODS: Four subjects with chronic poststroke hemiparesis participated in this single-case study. The primary outcome measures were the Berg Balance Scale (BBS) and the Timed Movement Battery (TMB). A secondary outcome measure was the Stroke Impact Scale (SIS). The baseline testing phase varied for each subject and ranged from 4 to 7 weeks. The 8-week intervention phase consisted of 1.5-hour yoga sessions, 2 times per week, in the subject's home. The primary outcome data were collected each week, and the secondary outcome data were collected before the baseline testing phase and before and after the intervention phase. RESULTS: Subjects 1, 2, and 4 had improved TMB scores, and subjects 3 and 4 had improved BBS scores. DISCUSSION AND CONCLUSION: The results suggest that yoga may be beneficial to people who have had a stroke. Further investigation is warranted to further examine the effects of yoga in this population.